Blast loaded steel-concrete composite slab - Aizat, Alias; Amin, A. F. M. (Faculty Mechanical Engineering, UMP, 2021)
This paper presented a numerical investigation of a steel-concrete composite slab subjected to blast loads. The finite element model of the composite slab was developed and validated against experimental results. The validated finite element model of the composite slab then subjected to blast loads using CONWEP function in ABAQUS. A validation investigation was performed on CONWEP function by comparing the blast-pressure profiles from CONWEP against experimental data. Both validation studies showed that the developed finite element model of the composite slab and CONWEP agree reasonably well with test results. The fully restrained composite slab was subjected to four different blast loads with different explosive weights and standoff distances. The transient deformation of the composite slab after subjected to blast loads was investigated where as predicted the deformation of the composite slab was influenced by the blast pressure, which is affected by the weight of explosive and standoff distance. This study also investigated the mode of failure where it was determined flexural failure at the midspan is the main mode of failure accompanied with concrete tensile failure at the supports. The thickness of the profiled deck and the coeffecient of friction influenced the dynamic response of the composite slabs. Increasing the thickness reduces the maximum displacement of the composite slabs. Increasing the coefficient of friction reduces the maximum dislacement but once the coefficient of friction reach its optimum value, no positive benefit is gained.